A Rainbow Structural‐Color Chip for Multisaccharide Recognition. Issue 24 (4th May 2016) - Qin, Meng; Huang, Yu; Li, Yanan; Su, Meng; Chen, Bingda; Sun, Heng; Yong, Peiyi; Ye, Changqing; Li, Fengyu; Song, Yanlin
Abstract: A critical requirement for the successful recognition of multiple analytes is the acquisition of abundant sensing information. However, for this to be achieved requires massive chemical sensors or multiplex materials, which complicates the multianalysis. Thus, there is a need to develop a strategy for the facile and efficient recognition of multiple analytes. Herein, we explore the angle‐dependent structural colors of photonic crystals to provide abundant optical information, thereby generating a rainbow‐color chip to realize the convenient recognition of multiple analytes. By simply using a multiangle analysis method, the monophotonic crystal matrix chip can differentially enhance fluorescence signals over broad spectral ranges, thereby resulting in abundant sensing information for highly efficient multiple analysis. Twelve saccharides with similar structures, as well as saccharides in different concentrations and mixtures, were successfully discriminated. Abstract : Color vision : A photonic crystal that recognizes saccharides specifically allows abundant optical information to be obtained in the form of structural color. The use of a multiangle analysis method enables fluorescence signals in various spectral regions to be differentially enhanced. This approach enabled 12 saccharides with similar structures, as well as saccharides at different concentrations and in mixtures, to be successfully discriminated.